УПРАВЛЯЕМОЕ ФИЛЬТРОКОМПЕНСИРУЮЩЕЕ УСТРОЙСТВО ДЛЯ АВТОНОМНОЙ ЭЛЕКТРОЭНЕРГЕТИЧЕСКОЙ СИСТЕМЫ С МОЩНЫМИ ПРЕОБРАЗОВАТЕЛЯМИ - Жук, А.К.; Жук, Д.А.; Криворучко, Д.В.; Степенко, С.А. (Інститут електродинаміки НАН України, Київ, 2016)
Directions of improvement of controlled filter-compensator gear for the autonomous electric power system with semiconductor converters, which contains resonant LC-filter and reactor compensator with pulse-wide modulation are considered. The terms of concordance of frequency characteristics of electric power system with spectrums of harmonics, which are generated in to the network by semiconductor converters and reactor compensator were established. Possibility and expedience of EMI filter application for reactor compensator as a part of controlled filter-compensator gear were shown. References 3, figures 4.